The impact of the massive open online course C19_SPACE during the COVID-19 pandemic on clinical knowledge enhancement: a study among medical doctors and nurses - Cecconi, Maurizio; Barth, Anita; Szőllősi, Gergő József; Istrate, Gizella Melania; Alexandre, Joel; Duska, Frantisek; Schaller, Stefan J; Boulanger, Carole; Mellinghoff, Johannes; Waldauf, Peter; Girbes, Armand R J; Derde, Lennie; et al. (Intensive care medicine, 2024)
PURPOSE: During the initial phase of the pandemic, healthcare professionals faced difficulties due to the limited availability of comprehensive learning resources on managing patients affected with coronavirus disease 2019 (COVID-19). The COVID-19 Skills Preparation Course (C19_SPACE) was tailored to meet the overwhelming demand for specialized training. The primary objective of this study was to assess the efficacy and impact of this program on enhancing clinical knowledge and to identify factors affecting this improvement. METHODS: As part of the project, data were collected prospectively to measure the baseline knowledge. After the descriptive statistics, multiple and multivariate logistic regression models were executed to identify the factors associated with knowledge increase. RESULTS: The final sample included 3140 medical doctors (MDs) and 3090 nurses (RNs). For the primary analysis, the mean value of the baseline knowledge test score of MDs was 62.41 (standard deviation, SD = 13.48), and it significantly (p < 0.001) increased to 84.65 (SD = 11.95). Factors influencing overall knowledge scores were female sex (AOR = 1.34 [1.04-1.73]), being a specialist qualified for intensive care medicine (adjusted odds ratio, AOR = 0.56, [0.33-0.96]), and performance on the pre-test (AOR = 0.91, [0.90-0.92]). As for the RNs, the mean value of the total knowledge score was 63.25 (SD = 13.53), which significantly (p < 0.001) increased to 81.51 (SD = 14.21). Factor associated with knowledge was performance on the pre-test (AOR = 0.92 [0.92-0.93]). CONCLUSIONS: C19_SPACE effectively increased the clinical knowledge of doctors and nurses. The effect was more pronounced in the program's target group of healthcare workers with less experience in the intensive care unit (ICU). Other factors associated with knowledge enhancement were sex and being a specialist in intensive care.
Keywords: klinické kompetence; Pandemics; SARS-CoV-2; Middle Aged; mužské pohlaví; COVID-19; Prospective Studies; Adult; Clinical Competence; zdravotní sestry; ženské pohlaví; Humans; prospektivní studie; distanční studium; Education, Distance; lidé středního věku; dospělí; pandemie; Female; lékaři; Nurses; Physicians; lidé; Male